ANALYSIS OF FIGURATIVE LANGUAGE IN MALIBU NIGHTS ALBUM - Sarah Alifiannisa; Dian Wulandari (Jurnal Sosial Humaniora dan Pendidikan, 2024)
The research aims to find out types of figurative language used in the Malibu Nights album and the most dominant figurative language that is used. The data source is obtained from an album called Malibu Nights from one of LANY's discography. This research used the qualitative method and Perrine’s theory in collecting and analyzing the data. From the 26 data, 5 types of figurative language consist 6 items of metaphor, 5 items of personifications, 9 items of hyperbole, 5 items of simile, and 1 item of paradox. From the data that has been found, it can be concluded that the dominant figurative language that are used in Malibu Nights album is hyperbole with total of 9 items.